Numerical Study of Bach-bladed Savonius Wind Turbine with Varying Blade Shape Factor - Kelvin Ibrahim; Vivien Suphandani Djanali; Nur Ikhwan (JMES The International Journal of Mechanical Engineering and Sciences, 2020)
Savonius wind turbine with Bach-profile blades is considered in this study. Previous studies have shown that a rotor with the Bach-profile blade produces better performance than a standard Savonius turbine. This study focuses on the blade shape factor variations of the Bach-profile blade to give the best performance. Two-dimensional unsteady simulations are performed with moving mesh. The configuration being tested is the Savonius rotor with Bach-profile blades with an arc angle of 135◦ . The blade shape factor is varied 0.2, 0.3, 0.4 at a constant freestream velocity of 4 m/s, with a corresponding Reynolds number of 20,000. The k-ω Shear Stress Transport turbulence model was used, with secondorder discretization schemes for the pressure and momentum equations. The boundary conditions were set as velocity inlet for the inlet, outflow for the outlet, and walls for the blade surfaces. The top and bottom sides were set as symmetric. Results showed that the configuration with a shape factor of 0.4 gave the best performance among the others. This configuration gave a higher moment coefficient and power coefficient of about 6.8% and 7.3%, respectively. Results extracted from the simulation includes the flow structure, and the distribution of the pressure coefficients along the blade surface.